Competency for leaders - Ismie Roha, Mohamed Jais; Salmiah, Abdul Hamid; Haryana, Mohd Hairi; Fauziah, Hassan (Penerbit UiTM Press, 2022)
The emergence of the COVID-19 pandemic in the year 2020 has brought the whole world to an abrupt halt. Existing strategic planning was no longer relevant as organisations encountered unprecedented Volatility, Uncertainty, Complexity and Ambiguity (VUCA) world. The leadership of HLIs must be agile in maneuvering the challenges by establishing a common purpose and clear communications to allow rapid decision-making, which ensures long-term sustainability, creatingnetworks of local teams with clear and accountable roles via empowerment and flat structures. In addition, an agile leader will also provide people with the technology they need, which is the core of every aspect of an organisation to sustain and be competitive. This book is designed as a reference for HLI leaders, academicians, researchers, and individuals interested in understanding the agile leadership and actions needed to ensure that the people and the organisation strive in the future.